A low-cost wideband SIW antenna with bilateral slots on FR4 Epoxy for Ku-band applications - Al Gburi, Ahmed Jamal Abdullah; Chrij, Dounia; Khabba, Asma; El Ouad, Zakaria; Sellak, Lahcen; Amadid, Jamal; Benkhadda, Omaima; Ibnyaich, Saida; Zeroual, Abdelouhab (Electromagnetics Academy, 2025)
This article presents an approach to expanding the impedance bandwidth of a bilateral slotted antenna backed by a substrateintegrated waveguide (SIW) cavity using high-order radiation modes. By trimming a section of the conductive ground plane and connecting one side of the bottom long slot with a via, the three hybrid modes of the cavity are perturbed and merged to achieve a broad bandwidth. The optimized antenna is fed by a microstrip transmission line for Ku-band applications, demonstrating an impressive impedance bandwidth of 6.68 GHz (a fractional bandwidth of 41%) ranging from 12.82 GHz to 19.5 GHz, with a peak gain of 6.6 dBi. Compared to previous studies, the proposed antenna offers not only a wide bandwidth but also a compact size, with dimensions of 29.7 × 22 mm2 , and its electrical dimensions are 1.6λ0 × 1.19λ0, where λ0 is the free space wavelength at the center frequency fcenter = 16.16 GHz. Additionally, it has low production costs due to fabrication on an inexpensive FR4 substrate. The antenna was initially simulated using HFSS software, and to validate the accuracy of the results, it was also analyzed with CST Microwave Studio. Moreover, a prototype was constructed for experimental testing, with measured results showing strong agreement with the simulations.